2022
DOI: 10.1111/petr.14218
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac allograft vasculopathy: A review

Abstract: Background Heart transplantation has become the standard of care for pediatric patients with end‐stage heart disease, and outcomes have consistently improved over the last few decades. CAV, however, remains a leading cause of morbidity and mortality in heart transplantation and is the leading cause of death beyond 3 years post‐transplantation. We sought out to provide an in‐depth overview of CAV in the pediatric heart transplant population. Methods Database searches were conducted in both Medline and Embase on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…25 Despite this, many pediatric heart transplant programs incorporate statin therapy into their post-transplant protocols. 22 Recent research is focused on the immune mechanisms of CAV and the role of interleukin-6 (IL-6) in mediating CAV; a randomized controlled trial of tocilizumab, an IL-6 receptor antagonist, in adult heart transplant recipients is ongoing with estimated completion in April 2025. 26…”
Section: Ardiova Scul Ar Dis E a S Ementioning
confidence: 99%
See 1 more Smart Citation
“…25 Despite this, many pediatric heart transplant programs incorporate statin therapy into their post-transplant protocols. 22 Recent research is focused on the immune mechanisms of CAV and the role of interleukin-6 (IL-6) in mediating CAV; a randomized controlled trial of tocilizumab, an IL-6 receptor antagonist, in adult heart transplant recipients is ongoing with estimated completion in April 2025. 26…”
Section: Ardiova Scul Ar Dis E a S Ementioning
confidence: 99%
“…21 CAV is a progressive form of vascular intimal proliferation that leads to obliteration of the vascular lumen. 22 The causes of CAV are poorly understood but likely include some combination of immune mechanisms (e.g., antibody-mediated rejection) in addition to traditional nonimmune cardiac risk factors, including dyslipidemia, hypertension, diabetes, and obesity. mTOR inhibitors have been proposed as an alternative immunosuppressive agent to decrease the onset or progression of CAV, but a recent retrospective review of showed increased rates of rejection and CAV in children treated with mTOR inhibitors, though the authors did not feel the association with CAV was likely to be causal.…”
Section: Ardiova Scul Ar Dis E a S Ementioning
confidence: 99%
“…Cardiac allograft vasculopathy is the leading cause of graft failure, affecting almost 50% of pediatric heart transplant recipients by 15 years post‐transplant 2 . There has been no significant improvement in the prevention or treatment of this complication over the past 20 years, with repeat transplantation representing the only viable management option 3,4 . Despite this, repeat transplantation is rare, accounting for less than 5% of all pediatric transplants 1,5 .…”
Section: Introductionmentioning
confidence: 99%
“…2 There has been no significant improvement in the prevention or treatment of this complication over the past 20 years, with repeat transplantation representing the only viable management option. 3,4 Despite this, repeat transplantation is rare, accounting for less than 5% of all pediatric transplants. 1,5 A diagnosis of congenital heart disease and a history of previous transplantation are each independently associated with worse survival following pediatric heart transplantation.…”
mentioning
confidence: 99%
“…
C hronic rejection in heart transplant (HTx) presents as cardiac allograft vasculopathy (CAV), manifesting as progressive and diffuse intimal proliferative arteriosclerosis. 1 CAV can cause late graft failure and death after pediatric HTx. Approximately half of pediatric HTx recipients develop CAV during the first 15 posttransplant years.
…”
mentioning
confidence: 99%